2020
DOI: 10.1021/acsinfecdis.0c00121
|View full text |Cite
|
Sign up to set email alerts
|

Potency Increase of Spiroketal Analogs of Membrane Inserting Indolyl Mannich Base Antimycobacterials Is Due to Acquisition of MmpL3 Inhibition

Abstract: Chemistry campaigns identified amphiphilic indolyl Mannich bases as novel membrane-permeabilizing antimycobacterials. Spiroketal analogs of this series showed increased potency, and the lead compound 1 displayed efficacy in a mouse model of tuberculosis. Yet the mechanism by which the spiroketal moiety accomplished the potency "jump" remained unknown. Consistent with its membrane-permeabilizing mechanism, no resistant mutants could be isolated against indolyl Mannich base 2 lacking the spiroketal moiety. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
(132 reference statements)
0
17
0
1
Order By: Relevance
“…Incorporation of a spiroketal moiety in the Mannich base caused a 10-fold increase in potency (4). Interestingly, mutants resistant to the spiroketal analogs could be isolated and mapped to the mycolic acid transporter MmpL3 (5). Biochemical, metabolic, computational and structure-activity-relationship analyses revealed that the potency improvement was caused by the acquisition of a second mechanism of action due to the inclusion of the spiroketal moiety (5).…”
Section: Downloaded Frommentioning
confidence: 99%
See 4 more Smart Citations
“…Incorporation of a spiroketal moiety in the Mannich base caused a 10-fold increase in potency (4). Interestingly, mutants resistant to the spiroketal analogs could be isolated and mapped to the mycolic acid transporter MmpL3 (5). Biochemical, metabolic, computational and structure-activity-relationship analyses revealed that the potency improvement was caused by the acquisition of a second mechanism of action due to the inclusion of the spiroketal moiety (5).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Interestingly, mutants resistant to the spiroketal analogs could be isolated and mapped to the mycolic acid transporter MmpL3 (5). Biochemical, metabolic, computational and structure-activity-relationship analyses revealed that the potency improvement was caused by the acquisition of a second mechanism of action due to the inclusion of the spiroketal moiety (5). In addition to permeabilizing the membrane, spiroketal analogs of the indolyl Mannich bases (SIMBs) inhibit the flippase activity of the transmembrane MmpL3 protein and hence the transport of mycolic acids from the cytoplasm to the periplasmic space (5).…”
Section: Downloaded Frommentioning
confidence: 99%
See 3 more Smart Citations